Body growth assessment in children with IgE-mediated cow's milk protein allergy fed with a new amino acid-based formula - Nocerino, Rita; Coppola, Serena; Carucci, Laura; Paparo, Lorella; De Giovanni Di Santa Severina, Anna Fiorenza; Berni Canani, Roberto (Frontiers in Allergy, 2022)
Background Amino acid-based formula (AAF) is a relevant dietary option for non-breastfed children. The present study was designed to evaluate the body growth pattern in cow's milk protein allergy (CMPA) children treated for 6 months with a new AAF. Methods This was an open-label, single arm study evaluating body growth pattern in immunoglobulin E (IgE)-mediated CMPA infants receiving a new AAF for 6 months. The outcomes were anthropometry (weight, length, head circumference), adherence to the study formula and occurrence of adverse events (AEs). Results Fifteen children [all Caucasian and born at term; 53.3% born with spontaneous delivery; 80% male; 80% with familial allergy risk; mean age (±SD) 3 ± 2.5 months at IgE-mediated CMPA diagnosis; mean age (±SD) 16.7 ± 5.9 months at enrolment, mean total serum IgE (±SD) 298.2 ± 200.4 kU/L] were included and completed the 6-month study. Data from fifteen age- and sex-matched healthy controls were also adopted as comparison. At baseline, all CMPA patients were weaned and were receiving the new AAF. All 15 patients completed the 6-month study period. For the entire CMPA pediatric patients’ cohort, from baseline to the end of the study period, the body growth pattern resulted within the normal range of World Health Organization (WHO) growth references and resulted similar to healthy controls anthropometric values. The formula was well tolerated. The adherence was optimal and no AEs related to AAF use were reported. Conclusions The new AAF ensured normal growth in subjects affected by IgE-mediated CMPA. This formula constitutes another suitable safe option for the management of pediatric patients affected by CMPA.